Levels of PCDDs, PCDFs, and PCBs in the blood of the non-occupationally exposed residents living in the vicinity of a chemical plant in the Czech Republic - Cerná, Milena; Kratenová, Jana; Zejglicová, Kristýna; Brabec, Marek; Malý, Marek; Smíd, Jirí; Crhová, Sárka; Grabic, Roman; Volf, Jaroslav (Chemosphere, 2007)
In 2003, concentrations of altogether 17 PCDD/Fs congeners and 12 non-ortho and mono-ortho dioxin-like PCBs were measured in the blood of 60 randomly selected adults who lived in three settlements surrounding a chemical plant that had been producing chlorinated herbicides (mainly HCHs, HCB, pentachlorophenole, 2,4,5-T) in the 1960's; subjects consuming home-produced animal foods were chosen. Twenty blood donors with similar characteristics from the locality with about 80 km distance were used as control subjects. The factors that influenced the dioxin levels were investigated on the basis of a questionnaire. The aim of our study was to find out whether the residents living in the surroundings of the chemical plant are at a greater exposure risk than the controls. To calculate TEQ values, WHO-TEFs were used. The concentrations of four PCDD and six PCDF congeners were below the LOD in more than 50% of samples. Significantly higher WHO-TEQ levels (p<0.05) were found for PCDDs, PCDFs, or PCBs in all three followed up groups compared with controls. The geometric means of the total TEQ values for PCDD/F/PCBs were 43.8, 50.2, and 40.0 pg/g fat compared to 23.2 pg/g fat in the control. The percentages of TEQ due to the measured congeners in exposed groups were 9-10.3% for PCDDs, 20.5-26.9% for PCDFs, 19.2-23.1% for coplanar and 43.6-47.2% for mono-ortho PCBs. In control, the percentage of TEQ was 11.6, 26.7, 24.1, and 37.5%. PCBs, predominantly PCB156, followed by PCB126 contributed 60 to 70% of the total TEQ value. Positive correlation of the PCDD/PCDF/PCB blood levels with age and with consumption of locally produced eggs was found.
Keywords: Environmental Pollutants; monitorování životního prostředí; látky znečišťující životní prostředí; Population Surveillance; polychlorované bifenyly; benzofurany; Time Factors; Česká republika; Middle Aged; Environmental Monitoring; Polychlorinated Dibenzodioxins; Adult; Czech Republic; surveillance populace; Chemical Industry; chemický průmysl; Polychlorinated Biphenyls; bydlení; Dibenzofurans, Polychlorinated; Humans; zeměpis; polychlorované dibenzofurany; Housing; časové faktory; lidé středního věku; polychlorované dibenzodioxiny; dospělí; Geography; Benzofurans; lidé